Psikologi Pendidikan Islam dalam Al Qur’an - Putri Firdaus Fahmi; Siti Rohimah (Lembaga Yasin AlSys, 2026)
The Qur’an, as the primary source of Islamic teachings, gives considerable attention to the cultivation of the human soul through psychological concepts such as nafs, qalb, ‘aql, and ruh. The study of these concepts is important because Islamic education is oriented not only toward the mastery of knowledge but also toward character formation, emotional control, learning motivation, and the psychological health of students. This study aims to examine the concept of human psychology from the perspective of the Qur’an, explain the principles of Islamic educational psychology contained within it, analyze the views of scholars, particularly Imam Al-Ghazali and Ibnu Qayyim Al-Jauziyyah, and describe their implications for the educational process. This study used a literature review method with a descriptive-analytical qualitative approach. Data were obtained through an examination of Qur’anic verses related to educational psychology, character formation, motivation, emotional regulation, as well as the views of scholars and thinkers in Islamic educational psychology, and were then analyzed interpretatively to identify their relevance in the context of Islamic education. The findings show that the concept of psychology in the Qur’an includes three main principles, namely fitrah, tazkiyatun nafs, and the use of reason in the learning process. The principle of fitrah affirms the basic human potential to accept truth and develop morally, while tazkiyatun nafs plays a role in purifying the soul, self-control, and character formation. Meanwhile, the use of reason serves as an important basis for developing understanding, awareness, and responsibility in learning. These findings confirm that the Qur’an offers a comprehensive foundation for the development of Islamic educational psychology oriented toward the intellectual, spiritual, moral, and emotional balance of students. The implications of this study indicate the importance of Islamic learning strategies that not only emphasize cognitive aspects but also strengthen character development and students’ mental health as part of efforts to form individuals with noble character and an integrated personality.